Physical and chemical characteristics of fruits from different orange canopy/rootstock combinations grown in the brazilian semiarid - Santos, Luciana Martins; Calgaro, Marcelo; Bastos, Debora Costa; Mendonça, Andrea Vita Reis; Bezerra Ferreira, Pedro Paulo; Silva, Sebastião de Oliveira e; Melo Chaves, Agnaldo Rodrigues de (Comunicata Scientiae, 2021)
The orange trees ’Pera’/lemon ’Cravo’ combination has predominated in national territory, and new oranges trees canopies/rootstock combinations citrus have been availability in breeding programs to provide for productive sector. Thus, the objective of this work was to evaluate the physical and chemical characteristics of fruits orange trees from canopy/rootstock different combinations grown in Brazilian semiarid. The experimental design was in randomized blocks, in a factorial scheme with three canopy and four rootstock cultivars, with three replications. The orange trees used were ’Pera’, ’Natal’ and ’Sincorá’, while for the rootstocks the lemon ’Cravo Santa Cruz’, the mandarin ’Sunki’ Tropical selection, and the citrandarins ’Indio’ and ’Riverside’. The results obtained showed that factors acted independently in mass and diameter fruit, seeds number, juice yield, skin luminosity and pulp, chromaticity and hue angle pulp, ºBrix and acids contents. However, it was different in shell thickness, chromaticity and hue angle of the shell and SS/AT ratio. Was possible conclude that ’BRS 002 – Sincorá’ presented best results for physical and chemical analysis, and lemon ’Cravo Santa Cruz’ and Tangerine ’Sunki’ Tropical selection influenced the canopies to the best results of the physical and chemical analysis, respectively. All combinations showed low juice yield.